Urdu ka guldasta (Khususi Isha'at) Champa (for class 6) - Fouzia ahsan farooqui (Oxford University Press; Pakistan, 2022)
Champa Class 6 is an engaging textbook designed to enhance the knowledge and skills of sixth-grade students through a range of lessons, activities, and stories.